Poligami Dalam Timbangan Maqashid Syariah Dan Hukum Undang-Undang Di Indonesia: Poligami Dalam Timbangan Maqashid Syariah Dan Hukum Undang-Undang Di Indonesia - ahsanu_amala, aldiwa amiku (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
The aim of this research is to find out how the scales of polygamy in the Law and Maqashid Syariah prescribe polygamy in Islamic teachings. The research method used in this research is quantitative with literature review research. Research data used in writing is in the form of books, research journals, online news and websites. Data analysis in this research used three stages - data reduction, presentation, and drawing conclusions. The results of the research show that polygamy is still permitted in Indonesia with several applicable requirements in accordance with the law. The Maqshid Syariah in polygamy includes five aspects, protecting religion (Hifdzu din), protecting the soul (Hifdzu Nafs), protecting reason (Hifzu Aql), protecting property (Hifdzu Mal), protecting offspring (Hifdzu Nasl).